College-Bound Students' Attitudes about Investments and The Stock Market - Deshpande, Shreya S.; Jadhav, Sudarshan D. (ASEAN Journal of Educational Research and Technology, 2023)
A well-organized marketplace where different buyers and sellers can purchase and sell shares is the stock market. This study's primary goal is to examine students' awareness of and preferences for stock market investments. The information used in the study was gathered from primary sources. The results of this study will assist investors invest in the stock market with greater knowledge and assurance. This study will contribute to the investigation of student awareness of investing. The purpose of the study is to determine the student's interest in investing and the factors that prevent them from doing so. The study will make it easier to gauge how satisfied students are with their stock market investments. To help other researchers make more accurate conclusions about the results, the limitations and suggestions are presented at the end.